The AI Commander : centaur teaming, command, and ethical dilemmas - Johnson, James (New York: Oxford: Oxford University Press, 2024)
"What do emerging technologies like artificial intelligence (AI) mean for the role of humans in war? This book addresses the largely neglected question of how the fusion of machines into the war machine will affect the human condition of warfare. Specifically, it investigates the vexing, misunderstood, and at times contradictory, ethical, moral, and normative implications-whether incremental, transformative, or revolutionary-of synthesizing man and machine in future algorithmic warfare-or AI-enabled 'centaur warfighting.' At the heart of these vexing questions are whether we are inevitably moving toward a situation where AI-enabled autonomous weapons will make strategic decisions in place of humans and thus become the owners of those decisions. Can AI-powered systems replace human commanders? And, more importantly, should they? The book argues that AI cannot be just passive and neutral force multipliers of human cognition"
Keywords: Artificial Intelligence -- Military Applications; Military Ethics; Military Planning -- Decision Making